Problematika Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Tsanawiyah Asy-Syafiiyah Gondang Tulungagung - Az-Zahra Eldauzi; Jani Jani (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This research is motivated by the discovery of several problems in learning Social Sciences at MTs Asy-Syafiiyah Gondang Tulungagung. This greatly influences the learning process for both teachers and students in the subject of Social Sciences. The purpose of this study is: To determine the problems faced in the process of learning Social Studies at MTs Asy-Syafiiyah Gondang Tulungagung in the 2024/2025 Academic Year along with efforts to overcome problems in the process of learning Social Studies at MTs Asy-Syafiiyah Gondang Tulungagung. This study uses a descriptive qualitative method using in-depth interviews, participant observation and documentation as a form of data collection, data sources in the study. The problems faced in the Social Studies learning process include learning methods that are less interesting and interactive, lack of learning motivation from students, lack of training or workshops for teachers, limited supporting facilities in the learning process, and less than optimal learning evaluation.